2018
DOI: 10.1101/396416
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metformin Intervention Prevents Cardiac Dysfunction in a murine model of Adult Congenital Heart Disease

Abstract: Congenital heart disease (CHD) is the most frequent birth defect worldwide and the number of adult patients with CHD, now referred to as ACHD, is increasing. However the mechanisms whereby ACHD predisposes patients to heart dysfunction are still unclear. ACHD is strongly associated with metabolic syndrome, but how ACHD interacts with poor modern lifestyle choices and other comorbidities, such as hypertension, obesity and diabetes, is mostly unknown. Using a genetic mouse model of ACHD we showed that ACHD mice … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Evidence backing the pleiotropic effects of metformin in reducing CVD-related events necessitates further exploration with regard to the mechanism of drug action in various tissue compartments. The recent evidence pointing towards its therapeutic benefit in heart failure with persevered ejection fraction in clinical and preclinical studies underlines the need to explore the breadth of the pleiotropic systemic effects of metformin [70]. Recent study also reported that metformin offers therapeutic benefit during heart failure with preserved ejection fraction by lowering titin-based passive stiffness in mice model [71], is associated with improved survival and decreased incidence of adverse cardiac events in peripheral arterial disease patients [72] and with a lower below-the-knee arterial calcification score [73].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence backing the pleiotropic effects of metformin in reducing CVD-related events necessitates further exploration with regard to the mechanism of drug action in various tissue compartments. The recent evidence pointing towards its therapeutic benefit in heart failure with persevered ejection fraction in clinical and preclinical studies underlines the need to explore the breadth of the pleiotropic systemic effects of metformin [70]. Recent study also reported that metformin offers therapeutic benefit during heart failure with preserved ejection fraction by lowering titin-based passive stiffness in mice model [71], is associated with improved survival and decreased incidence of adverse cardiac events in peripheral arterial disease patients [72] and with a lower below-the-knee arterial calcification score [73].…”
Section: Resultsmentioning
confidence: 99%
“…Recent study also reported that metformin offers therapeutic benefit during heart failure with preserved ejection fraction by lowering titin-based passive stiffness in mice model [71], is associated with improved survival and decreased incidence of adverse cardiac events in peripheral arterial disease patients [72] and with a lower below-the-knee arterial calcification score [73]. Moreover, metformin is able to prevent cardiac dysfunction in a murine model of adult congenital heart disease [70]. A proper understanding of these pleotropic effects will allow us to tailor the dose of the drug and remain abreast about its potential side effects in patients receiving them.…”
Section: Resultsmentioning
confidence: 99%
“…reduced the development of HF in spontaneously hypertensive, insulinresistant rats [118], prevented progression of cardiac dysfunction in a model of adult congenital heart disease [119], and improved myocardial function in a rat model of post-MI HF [120]. Finally, changes in the gut microbiome that may be specific to the pathogenesis of HF (including HFpEF) have been described during treatment with metformin, especially involving bacteria that produce short chain fatty acids [108,109].…”
Section: Mechanisms Of Potential Relevance To Heart Failurementioning
confidence: 99%